Analyzing Instructional Strategies in Science Education: A Dual Approach Combining Systematic Review and Secondary Qualitative Data Analysis - Şeyma Irmak; Duygu Yılmaz Ergül (e-Kafkas Eğitim Araştırmaları Dergisi)
This study employed a dual research approach, incorporating both systematic review and secondary qualitative data analysis, to investigate instructional strategies and their rationales utilized by pre-service and in-service science teachers (PaIST) in physics topics. We chose widely recognized and readily accessible sources with extensive study coverage, including Web of Science, SCOPUS, Taylor & Francis Online, and ProQuest. Only four studies that conformed to our inclusion and exclusion criteria were identified for examination. The analysis unfolded in two phases: first, the identification of instructional strategies employed by PaIST, and second, the exploration of the underlying rationales guiding their choices. Our findings revealed a diverse array of instructional strategies, encompassing direct instruction, thought experiments, demonstrations, hands-on activities, think-pair-share, peer teaching, laboratory exercises, discussion/questioning techniques, drama, and real-life narratives. The rationales underpinning these strategies were multifaceted, aiming to enhance student motivation, stimulate cognitive development, facilitate collaborative group work, and foster meaningful learning experiences. Despite evidence supporting the effectiveness of various external strategies such as STEM education, out-of-school learning, and project-based teaching on students, pre-service and in-service science teachers appear hesitant to adopt these methods. Further research is needed to explore the barriers and factors influencing their instructional choices.